Lupus anticoagulants in systemic lupus erythematosus: prevalence and clinical associations. - Padmakumar, K (1990)
The prevalence of lupus anticoagulant (LAC) and its relation with reported clinical associations has been determined in 55 patients with systemic lupus erythematosus (SLE) from northern India who were studied prospectively. Kaolin clotting time was used to screen for LAC, which was detected in seven (13%) of the patients. Significant associations were found between LAC and thrombotic events, onset of disease at an early age, and disease of shorter duration. No statistically significant association could be found between LAC and recurrent abortions, pulmonary hypertension, thrombocytopenia, and neurological manifestations. It is concluded that LAC is a useful marker for a subset of patients with SLE at risk of thromboembolic events.